Anti‐HLA alloantibodies of the IgA isotype in re‐transplant candidates part II: Correlation with graft survival. (25th March 2018) - Arnold, M.‐L.; Bach, C.; Heinemann, F. M.; Horn, P. A.; Ziemann, M.; Lachmann, N.; Mühlbacher, A.; Dick, A.; Ender, A.; Thammanichanond, D.; Schaub, S.; Hönger, G.; et al.
Summary: We reported previously on the widespread occurrence of anti‐HLA alloantibodies of the IgA isotype (anti‐HLA IgA) in the sera of solid‐organ re‐transplantation (re‐tx) candidates (Arnold et al., 2013 ). Specifically focussing on kidney re‐tx patients, we now extended our earlier findings by examining the impact of the presence and donor specificity of anti‐HLA IgA on graft survival. We observed frequent concurrence of anti‐HLA IgA and anti‐HLA IgG in 27% of our multicenter collective of 694 kidney re‐tx patients. This subgroup displayed significantly reduced graft survival as evidenced by the median time to first dialysis after transplantation (TTD 77 months) compared to patients carrying either anti‐HLA IgG or IgA (TTD 102 and 94 months, respectively). In addition, donor specificity of anti‐HLA IgA had a significant negative impact on graft survival (TTD 74 months) in our study. Taken together, our data strongly indicate that presence of anti‐HLA IgA, in particular in conjunction with anti‐HLA‐IgG, in sera of kidney re‐tx patients is associated with negative transplantation outcome.